2019
DOI: 10.1167/tvst.8.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Oxygen Saturation and Its Variation With Refractive Error and Axial Length

Abstract: Purpose: To evaluate the relationships between refractive error, axial length (AL), and retinal vascular oxygen saturation in an adult population. Methods: This was a hospital-based, prospective observational study. The left eyes of phakic adult subjects without media opacity were analyzed. Subjective undilated manifest refraction was performed, and refractive errors were defined as myopia (spherical equivalent [SE], ,À1 D), emmetropia (SE between À1 D and þ1 D) and hyperopia (SE .þ1 D). Retinal oximetry was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…They function mainly in the cytoplasm where they bind to protein and have roles in the regulation of localisation, cellular response to stimuli, and regulation of multicellular organismal processes. saturation, can be examined [5,6,21,22] . Studies have reported that choroid thickness tends to decrease in myopic patients [7] and in experimentally induced myopia [23] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They function mainly in the cytoplasm where they bind to protein and have roles in the regulation of localisation, cellular response to stimuli, and regulation of multicellular organismal processes. saturation, can be examined [5,6,21,22] . Studies have reported that choroid thickness tends to decrease in myopic patients [7] and in experimentally induced myopia [23] .…”
Section: Resultsmentioning
confidence: 99%
“…With the development of optical coherence tomography technology, ophthalmologists and scientists can examine a larger area of ocular vessels, especially retinal and choroid vessels. The horizontal and vertical axes, as well as morphology and vascular oxygen saturation, can be examined [5, 6, 21, 22] . Studies have reported that choroid thickness tends to decrease in myopic patients [7] and in experimentally induced myopia [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Requiring only a dilated pupil to obtain a measurement, this technology has been implemented into clinical research examining patients with diabetes mellitus, cardiovascular disease, glaucoma, and high myopia. [6][7][8] The findings of these studies have provided a valuable insight into the retinal oxygen metabolism showing how oxygen consumption is reduced in patients suffering from glaucoma 9 and with increasing stages of DR. 10 Other studies have shown a change in oxygen parameters depending on visual field loss in glaucoma 4 and in hereditary conditions, including retinitis pigmentosa with characteristic loss of photoreceptors. 11,12 As with any novel technique, which is aimed at clinical testing, it is paramount to have a robust protocol that has a low test-retest variability and high specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 98%
“…6. 31,33,41 For each vessel segment, we implemented linear compensations by means of a backward regression model, with ODR serving as the dependent variable and the independent variables being potential confounders, i.e., laterality, optic disc area, spherical error, cylinder, vessel diameter, and quadrant pigmentation index (PI). Only the significant variables of the reduced (final) model were subsequently used to construct the following correction formula:…”
mentioning
confidence: 99%